2011
DOI: 10.1111/j.1574-6968.2011.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori CagA-mediated IL-8 induction in gastric epithelial cells is cholesterol-dependent and requires the C-terminal tyrosine phosphorylation-containing domain

Abstract: Upon infection of the gastric epithelial cells, the Helicobacter pylori cytotoxin-associated gene A (CagA) virulence protein is injected into the epithelial cells via the type IV secretion system (TFSS), which is dependent on cholesterol. Translocated CagA is targeted by the membrane-recruited c-Src family kinases in which a tyrosine residue in the Glu-Pro-Ile-Tyr-Ala (EPIYA)-repeat region, which can be phosphorylated, induces cellular responses, including interleukin-8 (IL-8) secretion and hummingbird phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…In previous studies, we demonstrated that reduced cellular cholesterol resulted in reduced VacA activity, as well as attenuated CagA-induced inflammation and decreased bacterial survival, in H. pylori -infected gastric epithelial cells (Lai et al, 2008, 2011; Wang et al, 2012). Specifically, reductions in cholesterol disrupt the integrity of lipid rafts, resulting in decreased type IV secretion system-mediated translocation of CagA into host cells (Hutton et al, 2010), thereby reducing downstream signaling and attenuating the inflammatory response (Lai et al, 2011). In the current study, we demonstrate that statin treatment yielded enhanced autophagy and reduced bacterial burdens in macrophages, followed by decreased levels of H. pylori -induced IL-1β production, suggesting that statin may attenuate H. pylori -induced pathogenesis via multiple mechanisms.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In previous studies, we demonstrated that reduced cellular cholesterol resulted in reduced VacA activity, as well as attenuated CagA-induced inflammation and decreased bacterial survival, in H. pylori -infected gastric epithelial cells (Lai et al, 2008, 2011; Wang et al, 2012). Specifically, reductions in cholesterol disrupt the integrity of lipid rafts, resulting in decreased type IV secretion system-mediated translocation of CagA into host cells (Hutton et al, 2010), thereby reducing downstream signaling and attenuating the inflammatory response (Lai et al, 2011). In the current study, we demonstrate that statin treatment yielded enhanced autophagy and reduced bacterial burdens in macrophages, followed by decreased levels of H. pylori -induced IL-1β production, suggesting that statin may attenuate H. pylori -induced pathogenesis via multiple mechanisms.…”
Section: Discussionmentioning
confidence: 89%
“…In particular, cholesterol plays a crucial role in H. pylori cell invasion and virulence (Lai et al, 2013). Depletion of cellular cholesterol not only attenuates H. pylori -induced pathogenesis (Hutton et al, 2010; Lai et al, 2011) but also promotes autophagy (Cheng et al, 2006), which has been shown to contribute to immune defense against invading pathogens (Levine et al, 2011; Deretic et al, 2013; Lai et al, 2015). Statins, inhibitors of HMG-CoA reductase that are widely prescribed for lowering serum cholesterol, have also been employed to reduce the risk of certain bacterial infections (Chow et al, 2010; Nseir et al, 2010; Boyd et al, 2012; Motzkus-Feagans et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…With H. pylori, previous studies have shown that cholesterol-rich microdomains are required for VacA binding, delivery, and intoxication of cells (20,28,41,48). Our previous studies demonstrated that translocation of CagA and the internalization of H. pylori in gastric epithelial cells are reduced significantly upon treatment of cells with M␤CD, thereby decreasing the pathogenesis induced by this bacterium (30,32). Moreover, we recently reported that the glucosylation of cholesterol in H. pylori is crucial for efficient cag type 4 secretion system (TFSS)-associated activity, which may due to the reorganization of membrane architecture (58).…”
Section: Discussionmentioning
confidence: 99%
“…The threshold was set above the non-template control background and within the linear phase of target gene amplification in order to calculate the cycle number at which the transcript was detected (denoted as C T ). NF-kB reporter luciferase assay RAW264.7 cells were plated in a 12-well plate and then transfected with a NF-kB-luc reporter plasmid (1 µg) using Lipofectamine 2000 (Invitrogen), as described previously [36]. The transfected cells were lysed, and luciferase assays were performed with the Dual-Luciferase Reporter Assay System and normalized by cotransfection with a b-galactosidase expression vector (Promega, MA, USA).…”
Section: Reverse Transcription and Quantitative Real-time Pcrmentioning
confidence: 99%